Estudo da zona fundida de uma junta soldada do aço ASTM A-36 com inconel 625 - Diniz, Nadie Katyllie Silva (2017)
Among the most important welding technologies for commercial applications in the steel and metallurgical industries are GMAW electric arc process. In this process the heat generated by an electric arc is used to fuse the junction area. However, multipass welding is subject to variations in phase composition and mechanical properties, due to the thermal input resulting from the process. In this way, the objective of this work is to study the melt zone of a joint welded between ASTM-A36 steel and Inconel 625. For this, the microstructure and characterization of mechanical properties of each weld bead was verified. The Optical Microscopy (OM), Vickers Microhardness and Modulus of Elasticity assays were performed for this purpose. The results show a microstructure with variation in the directions of dendritic growth, and the presence of intragranular and intergranular cracks, precipitates, pores and inclusions in the weld beads. In turn, the results of hardness and modulus of elasticity show small variations between the weld beads, due to the microstructures formed. As the results show, the quality of the melt pool is influenced by the thermal gradient generated by the multipass remelting zones, as well as its microstructure and mechanical performance.